2010
DOI: 10.4103/0974-8490.75451
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the cytotoxic potential of standardized aqueous and ethanolic extracts of a polyherbal mixture comprised of Nigella sativa (seeds), Hemidesmus indicus (roots) and Smilax glabra (rhizome)

Abstract: Background:A decoction (hot-water extract) comprised of Nigella sativa (seeds), Hemidesmus indicus (roots), and Smilax glabra (rhizome) has been reported to prevent chemically-induced hepatocarcinogenic changes in rats and to exert significant cytotoxic effects on human hepatoma (HepG2) cells. However, the decoction used in previous studies to determine cytotoxicity was not standardized. Further, during preparation of pharmaceuticals for clinical use, it is more convenient to use an ethanolic extract. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 14 publications
0
46
0
Order By: Relevance
“…MTT assay was carried out as previously described methods [12,13]. Cancer cells plated in 96 well plates were treated with different concentrations (6.25, 12.5, 25, 50 and 100 µg/mL) of compounds and incubated for 24, 48 and 72 h. After incubation, MTT reagent (20 μL of 1 mg/mLstock solution) was added to each well and plates were incubated for 4 h at 37 °C.…”
Section: Cytotoxic Assaymentioning
confidence: 99%
“…MTT assay was carried out as previously described methods [12,13]. Cancer cells plated in 96 well plates were treated with different concentrations (6.25, 12.5, 25, 50 and 100 µg/mL) of compounds and incubated for 24, 48 and 72 h. After incubation, MTT reagent (20 μL of 1 mg/mLstock solution) was added to each well and plates were incubated for 4 h at 37 °C.…”
Section: Cytotoxic Assaymentioning
confidence: 99%
“…The alcoholic extract of seed showed a significantly higher cytotoxic potential than the seed oil of Petroselinum sativum. This kind of difference in the cytotoxicity of different extracts have also been observed by Samarakoon et al (2010), explaining that this cytotoxicity is possibly due to the active components and herbal preparation (Samarakoon et al, 2010). Alcoholic seed extract (PSA) and seed oil (PSO) of P. sativum were also further investigated to determine their mechanism of cell death by observing them under phase contrast inverted light microscope.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, another study [50] carried out on standardized aqueous and ethanolic extracts of a plant mixture (Nigella sativa, Hemidesmus indicus, and Smilax glabra) determined their cytotoxic effects on human hepatoma (HepG2) cell lines. The study demonstrated that both extracts exhibited strong dose dependent cytotoxicity to HepG2 cells.…”
Section: Discussionmentioning
confidence: 99%